Food processing as a means for pesticide residue dissipation - Đorđević, Tijana; Đurović-Pejčev, Rada (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
Pesticides are one of the major inputs used for increasing agricultural productivity of crops. However, their inadequate application may produce large quantities of residues in the environment and, once the environment is contaminated with pesticides, they may easily enter into the human food chain through plants, creating a potentially serious health hazard. Nowadays, consumers are becoming more aware of the importance of safe and high quality food products. Thus it is pertinent to explore simple, cost-effective strategies for decontaminating food from pesticides. Various food processing techniques, at industrial and/or domestical level, have been found to significantly reduce the contents of pesticide residues in most food materials. The extent of reduction varies with the nature of pesticides, type of commodity and processing steps. Pesticides, especially those with limited movement and penetration ability, can be removed with reasonable efficiency by washing, and the effectiveness of washing depends on pesticide solubility in water or in different chemical solvents. Peeling of fruit and vegetable skin can dislodge pesticide residues to varying degrees, depending on constitution of a commodity, chemical nature of the pesticide and environmental conditions. Different heat treatments (drying, pasteurization, sterilization, blanching, steaming, boiling, cooking, frying or roasting) during various food preparation and preservation processes can cause losses of pesticide residues through evaporation, co-distillation and/or thermal degradation. Product manufactures, from the simplest grain milling, through oil extraction and processing, juicing/pureeing or canning of fruits and vegetables, to complex bakery and dairy production, malting and brewing, wine making and various fermentation processes, play a role in the reduction of pesticide contents, whereby each operation involved during processing usually adds to a cumulative effect of reduction of pesticides present in the material. There is diversified information available in literature on the effect of food processing on pesticide residues which has been compiled in this article.